The Importance of Digital Marketing Implementation for MSMEs in Indonesia: A Systematic Literature Review - Sunggara, Alvianno Difta; Nurhaliza, Putri; Ferdinand, Augusty Tae; Dirgantara, I Made Bayu (Research Horizon, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play a crucial role in supporting the national economy, contributing significantly to employment and the gross domestic product. However, many MSMEs have yet to fully leverage digital marketing due to limited digital literacy, restricted access to technology, and uneven infrastructure, particularly in remote areas. With the increasing use of the internet and social media in Indonesia, digital marketing strategies present a promising opportunity for MSMEs to expand their market reach, enhance customer engagement, and strengthen competitiveness. Through a systematic literature review, this study evaluates the implementation of digital marketing by MSMEs, including the use of social media and e-commerce platforms to increase brand visibility and foster more personal interactions with consumers. The analysis reveals that digital marketing enables MSMEs to enhance customer loyalty and reach wider markets at relatively low costs. Nevertheless, limitations in technological capability and low digital literacy remain significant barriers. This study highlights the importance of government support in the form of digital literacy training and equitable technology access to enable MSMEs to optimize their digital marketing strategies. Such support is essential to accelerate MSME digital transformation and improve their business sustainability in the competitive digital marketplace.